Immune system modulates the function of adult neural stem cells - Gonzalez-Perez, Oscar (2010)
New neurons are continuously produced in most, if not all, mammals. This Neurogenesis occurs only in discrete regions of the adult brain: the subventricular zone (SVZ) and the subgranular zone (SGZ). In these areas, there are neural stem cells (NSCs), multipotent and selfrenewing, which are regulated by a number of molecules and signaling pathways that control their cell fate choices, survival and proliferation rates. It was believed that growth and morphogenic factors were the unique mediators that controlled NSCs in vivo. Recently, chemokines and cytokines have been identified as important regulators of NSCs functions. Some of the most studied immunological effectors are leukemia inhibitory factor (LIF), ciliary neurotrophic factor (CNTF), interferon-gamma (IFN-γ), insulin-like growth factor-1 (IGF-1), tumor necrosis factor alpha (TNF-α), and the chemokines MCP-1 and SDF-1. These substances exert a considerable regulation on proliferation, cell-fate choices, migration and survival of NSCs. Hence, the immune system is emerging as an important regulator of neurogenic niches in the adult brain, but further studies are necessary to fully establish the biological meaning of these neural effects.